PENEGAKAN HUKUM KEJAHATAN HACKING DALAM PRESPEKTIF KEBIJAKAN HUKUM PIDANA DI INDONESIA - -, Sugiaryo (refleksi hukum)
AbstractHacking is a dark side of information and communication improvement bringing a very wide implication in all aspects of life, especially in close relation with enconomical crime. Hacking can be classified into two, they are usual crime-like hacking in which using information and communication technology as the supporting tools and also post internet-based hacking. In regards of such thing, then it is clearly must be considered on how does the method to enforce it. Hacking crime enforcement in Indonesia has many barrries. It is due to, among the others, electrical evident factor, the weak of information technological comprehension and its appliances for law enforcement, the less commplete available means and infrastructuress, the difficulties in presenting the victims and the weakness of public law awareness. For the hacking crime enforcement can be effectively implemented, besides using penal-characterized approach, it has to use non penal- characterized approach, that is the cultural approach in which are the dissemination method and ethics teaching on well-mannered computer usage through education media. Keywords : Law enforcement, hacking crime, crime code policy.